Pembentukan Karakter Siswa Melalui Profil Pelajar Pancasila di SDI Sokolo,o - Jehartu , Inovensius (Universitas Pahlawan Tuanku Tambusai, 2025)
Community service activities by lecturers and students of Flores University aim to provide understanding and comprehension to SDI Sokolo,o students to become intelligent and characterful individuals in accordance with the profile of Pancasila Students. The method used in this Community Service is in the form of delivering material using an offline infocus, simulation of problems that occur in social society and ending with a discussion and question and answer session The results of community service by lecturers and students of the Elementary School Teacher Study Program at Flores University can produce positive results, as seen from the enthusiasm and passion in participating in the provision of materials, questions and answers and discussions, as well as increasing understanding of the profile of intelligent and characterful Pancasila students who can foster a sense of nationalism and avoid bad company. Keywords: Pancasila students with character